Pemanfaatan Layanan Koleksi Tandon: Studi Kasus Perpustakaan Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Harahap, Nurhasanah; Sayekti, Retno; Fathurrahman, Muslih (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This thesis discusses the utilization of reservoir collection services at the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University Library. The aim to be achieved from this research is to find out how the reservoir collection service is utilized in the library of the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University. This research uses descriptive methods with a qualitative approach. By using data collection techniques, namely through observation, interviews and documentation. The informants in this research were librarians at the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University library. The results of this research show that the use of reserve collections (tandon) in the library of the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University. Reserve collection is a service for the use of textbooks which can be used as a reserve if the collection of textbooks provided in the circulation room has been borrowed by users. Reserve collections can only be photocopied. Its use cannot be loaned, it can only be read on the spot.